The Expressed Worries of Ukrainian Adolescents: A Quantitative Analysis of Chat Conversations During Active War - Peltonen, Kirsi; Hakala, Venla; Laajasalo, Taina; Stenvall, Elina; Mielityinen, Laura; Ellonen, Noora (SAGE PUBLICATIONS LTD, 2025)
Children and adolescents are particularly vulnerable to warfare and military violence. In this study, we aim to shed light on adolescents' experiences during times of war in a natural help-seeking environment. We use survey data obtained from two real-time online chat services designed for Ukrainian-speaking children and adolescents and explore young people's (n = 1,471) personal experiences during Russia's war of aggression against Ukraine. It was found that the most common topic that the adolescents wanted to talk about was mental well-being (30%), followed by the topic of personal relationships (29%) and home and family (22%). It is alarming that over 130 adolescents in our sample talked about self-harming or suicidality, and over a hundred expressed an unwillingness to live. As the war continues effective ways to support the mental well-being of young people and to treat mental health problems should be sought.